MISLEADING DIAGNOSIS OF SECONDARY ADRENAL INSUFFICIENCY IN A THAI PATIENT WITH RATHKE’S CLEFT CYST: A DIAGNOSTIC CHALLENGE IN PITUITARY INCIDENTALOMA - Chatchomchuan, Waralee; Thewjitcharoen, Yotsapon; Krittiyawong, Sirinate; Nakasatien, Soontaree; Himathongkam, Thep (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Rathke's cleft cysts (RCCs) are common sellar/suprasellar tumors with variable clinical presentations. We report a 56-year-old Thai male who initially received an incorrect diagnosis of secondary adrenal insufficiency despite presenting with weight loss and low basal serum cortisol. The patient complained of 8 kg weight loss, insomnia, and decreased sexual desire. Morning cortisol was 3.7 µg/dL. The patient had a prior diagnosis of adrenal insufficiency. At our hospital, serum cortisol was 3.0 µg/dL., ACTH was 10.3 pg/mL and other pituitary hormones were normal. The pituitary MRI revealed a small pituitary lesion consistent with Rathke's cleft cyst. ACTH stimulation test confirmed normal adrenal function. Psychological treatment for insomnia was initiated, and the patient improved without steroids. Follow-up tests remained unremarkable. It is crucial to conduct thorough clinical assessments and hormonal tests to avoid erroneous diagnoses of symptomatic Rathke's cleft cysts in patients with reduced basal cortisol levels